SYSTEM AND METHODS FOR X-RAY IMAGING AND A CONTRAST AGENT - ZHAO Ying (2021)
An x-ray apparatus and method can improve x-ray imaging in a variety of ways. For example, the improve x-ray apparatus can reduce scatter from x-ray images acquired by two-dimensional detectors. An improved 2D x-ray apparatus can provide 3D imaging for medical and/or industrial applications. An improved 2D x-ray apparatus and method can produce separate material imaging, and composition analysis for characterization and correlation of image, densitometry, and composition information of individual component or individual material within a single subject. Non-rotational 3D microscopy, combining 2D or 3D full field x-ray imaging and high resolution 2D or 3D x-ray microscopy or spectral absorptiometry and spectroscopy can achieve a higher resolution and wider field of view in x-ray imaging and quantitative analysis in 3D and real time. The x-ray apparatus can improve tracking and/or surgical guidance in time and/or space. Un aparato y un método de rayos X pueden mejorar la obtención de imágenes de rayos X de diversas formas. Por ejemplo, el aparato de rayos X mejorado puede reducir la dispersión de las imágenes de rayos X adquiridas por detectores bidimensionales. Un aparato de rayos X 2D mejorado puede proporcionar imágenes en 3D para aplicaciones médicas y/o industriales. Un método y aparato de rayos X 2D mejorado puede producir imágenes de materiales separados y análisis de composición para la caracterización y correlación de imágenes, densitometría e información de composición de componentes o materiales individuales dentro de un solo sujeto. La microscopía 3D no rotacional, que combina imágenes de rayos X de campo completo 2D o 3D y microscopía de rayos X 2D o 3D de alta resolución o absorciometría espectral y espectroscopía puede lograr una resolución más alta y un campo de visión más amplio en imágenes de rayos X y análisis cuantitativo en 3D y tiempo real. El aparato de rayos X puede mejorar el seguimiento y/o la guía quirúrgica en el tiempo y/o el espacio.